2022
DOI: 10.18632/aging.203890
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-associated tumor growth is promoted by 12-Lipoxygenase

Abstract: Radiation therapy is a commonly used treatment modality for cancer. Although effective in providing local tumor control, radiation causes oxidative stress, inflammation, immunomodulatory and mitogenic cytokine production, extracellular matrix production, and premature senescence in lung parenchyma. The senescence associated secretory phenotype (SASP) can promote inflammation and stimulate alterations in the surrounding tissue. Therefore, we hypothesized that radiation-induced senescent parenchymal cells in irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In a cancer framework, Patil and colleagues recently demonstrated that treatment of irradiated mice with a small molecule that tackles senescent cells (the senolytic agent ABT-737) was sufficient to reduce radiation-enhanced tumor growth through the control of the expression of 12-lipoxygenase (12-LOX), a molecule mediating the deleterious effects of senescence. These data demonstrate how radiation-induced senescence could support tumor growth, and identified a key component (12-LOX) of the oncogenic microenvironment [ 40 ]. Another compound, ABT-263, has demonstrated powerful senolytic activity against senescent breast cancer cells generated by radiation or chemotherapy [ 41 ].…”
Section: Tascs Have Both Tumor-suppressive and Oncogenic Impactsmentioning
confidence: 94%
“…In a cancer framework, Patil and colleagues recently demonstrated that treatment of irradiated mice with a small molecule that tackles senescent cells (the senolytic agent ABT-737) was sufficient to reduce radiation-enhanced tumor growth through the control of the expression of 12-lipoxygenase (12-LOX), a molecule mediating the deleterious effects of senescence. These data demonstrate how radiation-induced senescence could support tumor growth, and identified a key component (12-LOX) of the oncogenic microenvironment [ 40 ]. Another compound, ABT-263, has demonstrated powerful senolytic activity against senescent breast cancer cells generated by radiation or chemotherapy [ 41 ].…”
Section: Tascs Have Both Tumor-suppressive and Oncogenic Impactsmentioning
confidence: 94%
“…Combination of ALOX12 inhibitors (baicalein and BMD122) and radiation therapy have synergistic inhibitory effects on the growth of LNCaP and PC-3 prostate cancer cells as well as prostate cancer xenografts in SCID mice [237]. In a syngeneic tumor model of non-small cell lung cancer and melanoma, ALOX12 inhibition was showed to mitigate the effect of pre-radiation on the growth of pulmonary tumor nodules [238].…”
Section: Inhibitors Of Alox In Anti-cancer Therapiesmentioning
confidence: 99%
“…Radiation is known to induce a pro-inflammatory phenotype in microglia through activation of NF- B and mitogen-activated protein kinase (MAPK) pathways, resulting in increased cytokine secretion and neuronal apoptosis 79 . Radiation also induces senescence in tumor-associated macrophages (TAMs) 80 , while aiding in their recruitment in addition to that of activated peripheral monocytes and other immune cells 81 , both in non-glioma cancer models. Of note, the relative burden of therapy-induced senescence as a percentage of each cell population has yet to be determined, particularly in patient-derived specimens.…”
Section: The Deleterious Impacts Of Senescence In Gliomamentioning
confidence: 99%